New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific - Bastida-Zavala, J. Rolando; Buelna, Alondra Sofía Rodríguez; de León-González, Jesús Angel; Camacho-Cruz, Karla Andrea; Carmona, Isabel (Zootaxa, 2016)
Sabellids and serpulids are two well represented families in the polychaete fauna of the Tropical Eastern Pacific, with 31 and 34 species respectively; however, most records come from the Gulf of California or the western coast of Baja California Peninsula. Only a few records are from localities in the large expanse of the central and southern Mexican Pacific. Thus, sabellids and serpulids were collected from several shallow water habitats along the coast of Mexican Pacific, such as coastal lagoons, coral reefs, rocky shores and from man-made structures as marinas, piers and ships of several harbors; additionally, specimens from national collections were revised. More than 8,400 specimens of sabellids and serpulids from the states of Baja California, Baja California Sur, Sonora, Sinaloa, Michoacán, Guerrero, Oaxaca and Chiapas, and some specimens from Panamá and Perú were examined. In the present work we record new localities of four sabellids and 24 serpulids. One sabellid, Branchiomma bairdi, is an exotic/invasive species in Oaxaca, Sinaloa and Baja California Sur, while four species of serpulids are exotic and/or cryptogenic species: Ficopomatus uschakovi, Hydroides dirampha, H. elegans and H. sanctaecrucis. Additionally, the geographical range has been extended for five species: the sabellids Pseudobranchiomma punctata from Oahu, Hawaii to La Paz Bay, and Parasabella pallida from California to Puerto Escondido, Baja California Sur; and for three serpulids, Hydroides inermis from the Galápagos Islands to Agua Blanca, Oaxaca, H. gairacensis from Panamá to Puerto Ángel, Oaxaca, and H. panamensis from Panamá to Huatulco, Oaxaca and Faro de Bucerías, Michoacán. Hydroides cf. amri, previously recorded as H. brachyacantha from Oahu, Hawaii, is more similar to H. amri from Australia. The number of sabellids recorded for the Tropical Eastern Pacific increased to 33, the serpulid species to 35.